Interactions between progesterone and tumor necrosis factor-α in the regulation of primordial follicle assembly - Nilsson, Eric E (Reproduction, 2006)
Follicle assembly is the process by which groups or ‘nests’ of oocytes break down to form primordial follicles. The size of the primordial follicle pool is the major determinant of the reproductive lifespan of a female. Previously, progesterone (P(4)) has been shown to inhibit follicle assembly, while tumor necrosis factor-α (TNFα) has been shown to promote the apoptosis that is necessary for follicle assembly. The present study examines how TNFα and progesterone interact to regulate primordial follicle assembly. Ovaries were collected from newborn rats and placed in organ culture to examine the actions of P(4) and TNFα. P(4) was found to decrease primordial follicle assembly and increase the percentage of unassembled oocytes both in vitro and in vivo. TNFα treatment did not change the proportion of assembled follicles in cultured ovaries, but blocked the ability of P(4) to inhibit follicle assembly. Microarray analysis of the ovarian transcriptome revealed that progesterone treatment of the ovaries altered the expression of 513 genes with 132 only expressed after P(4) treatment and 16 only expressed in control ovaries. The majority of genes were up-regulated greater than twofold over control, with a small subset of 16 genes down-regulated. Categories of genes affected by P(4) are described including a group of extracellular signaling factors. The progesterone receptors expressed at the time of follicle assembly included the surface membrane progesterone receptors PGRMC1, PGRMC2, and RDA288. The nuclear genomic P(4) receptor was not expressed at appreciable levels. Progesterone increased the expression of several genes (TANK, NFkB, Bcl2l1, and Bcl2l2) involved in a signaling pathway that promotes cell survival and inhibits apoptosis. Observations indicate that P(4) acts through the surface membrane progesterone receptors to regulate primordial follicle assembly, and that TNFα can override the inhibitory actions of P(4) on follicle assembly. A major mechanism involved in the actions of P(4) is an increase in cell survival genes and inhibition of the apoptosis pathway. Observations provide insight into the hormonal regulation of primordial follicle assembly and lead to novel approaches to potentially manipulate follicle assembly and reproductive capacity.